PENGARUH PENAMBAHAN SIRTU TERHADAP NILAI CBR SUBGRADE RUAS JALAN KOYA TENGAH DISTRIK MUARA TAMI KOTA JAYAPURA (QUARRY SIRTU HARAPAN KABUPATEN JAYAPURA) - Alfian Adie Chandra (Faculty of Engineering, Planning and Architecture, Winaya Mukti University, 2021)
The problem of the bearing capacity of the subgrade is one of the most important thingsconsidered in a planning and work of a civil building construction. This matterbecause the soil functions as a medium that withstands the load or action of the constructionbuilt on it. Changes in weather and temperature in the field are factors that makeunstable ground. Many stabilizations have been carried out using cement soil, howeverrequires no small cost and also the results of the implementation of the soil stabilizationrelatively short-lived. Therefore, this research was conducted using a mixture ofsirtu with mixed variations of 15%, 20% and 30%. More variety of mixThe added sirtu causes the water content to decrease which will make the power value decreasethe bearing capacity of the soil increases, the value of the plastic limit increases, while the value of the liquid limit and indexthe plasticity of the soil decreases.